Magnum, Magnum - Lardinois, Brigitte,.; Magnum Photos, inc. (New York : Thames & Hudson, 2008)
A collection of more than four hundred photographs from the Magnum Agency that span the last sixty years and celebrate the unique environment and creativity of the agency and its photographers.
Includes bibliographical references (p. 566-567).
Adult
Keywords: Magnum Photos, inc; Magnum Photos, inc; Photography, Artistic; Photojournalism; Artistic photography; Photojournalism